2009
DOI: 10.1177/0022034509349926
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Craniofacial Structures: Facing the Challenge

Abstract: The human innate regenerative ability is known to be limited by the intensity of the insult together with the availability of progenitor cells, which may cause certain irreparable damage. It is only recently that the paradigm of tissue engineering found its way to the treatment of irreversibly affected body structures with the challenge of reconstructing the lost part. In the current review, we underline recent trials that target engineering of human craniofacial structures, mainly bone, cartilage, and teeth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 188 publications
(216 reference statements)
0
62
0
1
Order By: Relevance
“…The understanding of how normal wound healing and tissue formation occurs, together with recent advances in materials science, stem-cell research, and developmental biology have helped to find target molecules and pathways which can restore a patients' regenerative capacity. More and more evidence has shown that the "engineering" of irreversibly affected periodontal tissues is becoming feasible and such strategy could be developed for use as a clinical treatment [10].…”
Section: Biological Approaches To Periodontal Regenerationmentioning
confidence: 99%
“…The understanding of how normal wound healing and tissue formation occurs, together with recent advances in materials science, stem-cell research, and developmental biology have helped to find target molecules and pathways which can restore a patients' regenerative capacity. More and more evidence has shown that the "engineering" of irreversibly affected periodontal tissues is becoming feasible and such strategy could be developed for use as a clinical treatment [10].…”
Section: Biological Approaches To Periodontal Regenerationmentioning
confidence: 99%
“…Recreation or reorganizing the cranial and maxillofacial region up to the functional as well as esthetic requirement is thereby desired in the affected patients. [1] The present review mainly describes the research efforts concentrated in the methodology for orofacial reconstruction by making the use of stem cells, morphogens, scaffolds, and medical devices to a better denotative tissue engineering approach and the principle strategies of tissue engineering. This article also addressed the future potential and the significant advancements in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Facing the problems of large-area or irregular bony defects, the search for bone substitutes with satisfactory compatibility and sufficient strength became one of the major hotspots in bone tissue engineering 1,2) Degradability is one of the requirements of the ideal scaffold for bone tissue engineering. However, it is still unclear that whether degradation speed and bone formation rate is harmonious or not, and whether the degradation products have potential damage to human body or not 3,4) .…”
Section: Introductionmentioning
confidence: 99%